Exploring the impact of off the beaten path: Violence, women, and art. (March 2018) - Corcoran, Lynn; Lane, Annette
Abstract: What impact can the arts have on gender-based violence? Violence against women and girls is a global public health problem. Despite the volume of research amassed on this topic and recognition of the roots of this violence in the context of individuals, families, and communities as well as political and cultural systems, progress remains to be made toward recognizing and eliminating this violence. It is time to consider arts-based strategies as a catalyst for change. The purpose of this research study was to explore the impact of an art exhibition regarding violence against women and girls. The results of this study highlighted the following themes: personal stories of violence; learning and knowing; the power of art; and calls to action. These results pointed to the untapped potential of art as a strategy for making an impact on the issue of gender-based violence. Highlights: Violence against women and girls is a global public health problem. Content analysis was completed on comments from individuals attending an art exhibition on violence. Themes included: personal stories of violence; learning and knowing; power of art; calls to action. There is potential for arts-based strategies to provoke societal change.